Uji Aktivitas Antibakteri Ekstrak Etanolik Daun Sisik Naga (Drymoglossum piloselloides (L) Presl) terhadap Shigella dysenteriae ATCC 9361 dengan Metode Soxhletasi dan Perkolasi - Tinuk Wuryandari; Bambang Iskamto; Ismi Rahmawati (Fakultas Farmasi Universitas Setia Budi, 2010)
Leaves of Drymoglossum piloselloides [L.] Presl. were used as dysentery drug. The experiment was aimed to find out whether soxhletation and percolation extracts of Drymoglossum piloselloides [L.] Presl. leaves had antibacterial activity against Shigella dysenteriae ATCC 9361. Lleaves were dried and then blended to make powder. The extraction method used was soxhletation and percolation methods using ethanol 70% solvent. The obtained extract was evaporated until it was thick, and then the antibacterial activity test was conducted by dilution method against Shigella dysenteriae ATCC 9361. he concentrations of the test solutions were: 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.56%, 0.78%, 0.39%, 0.19%. The result of the experiment showed that soxhletation and percolation extracts had antibacterial activity against Shigella dysenteriae ATCC 9361 test bacteria. There was no difference in antibacterial activity between soxhletation extract and percolation extract against Shigella dysenteriae ATCC 9361 showed by minimum bactericidal concentration i.e. 50% both.